Profile of Students’ Inquiry Ability Variation on Heat Transfer - Hardiansyah M, Muhammad Rizal; Darwi, Rahmiati (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
This study is conducted to investigate the improvement of inquiry ability variation of students after applying inquiry learning model in 30 Junior High School, Makassar. Inquiry variation is amount of counseling intensity or guidance that is given by teacher in a learning. Inquiry variation can be seen based on five inquiry essential features such as applying question, deciding and collecting relevant evidence, making explanation based on the evidence, connecting the explanation with scientific references and communicate it. This research uses documentation study method. The sample of the research are 74 students of seventh grade that are taken by using random class sampling technique. Data collection technique uses observation sheet of inquiry ability variation. The data processing technique uses descriptive method. Data analysis result shows the improvement in five inquiry essential characteristics. It can be seen in the comparison between the first and the last meeting. In the first meeting, all of the inquiry essential characteristics were given by teacher, while in the last meeting, students can do the characteristics by themselves. However, it is only one characteristic that still need guidance from teacher like essential characteristic in deciding and collecting relevant evidence. The result of the study shows that the application of inquiry learning model can help students in improving inquiry ability variation that is better than the using of conventional learning model.